Strategi Pengembangan Kebun Raya Baturraden sebagai Objek Wisata - Hotimah, Oot; Iskandar, Rudi; Husmiati, Ratu; Oot Hotimah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
This study aims to formulate an appropriate alternative development strategy for the Baturraden Botanical Gardens. This strategy can make it easier for the management unit to develop the Baturraden Botanical Gardens even better. Primary data obtained through interviews and questionnaires. Baturraden Botanical Gardens as a vehicle for the environment has conservation and tourism functions. The development of the conservation function of the Baturraden Botanical Gardens is marked by the increasing collection of plants from time to time. Information obtained is that starting in 2014 the management of the Botanical Gardens of Baturraden and Tahura KGPAA Mangkunagoro I was separated through Pergub No. 20/2014. Based on the results of interviews, it was found that the public's view was that to develop the tourism potential of botanical gardens, botanical gardens should diversify activities, especially educational tours. Educational tours that are attractively packaged are one of the factors that can make visitors satisfied and want to visit again.